Differences Between Human and Murine Tau at the N-terminal End - Hernández, Félix; Merchán-Rubira, Jesús; Vallés-Saiz, Laura; Rodríguez-Matellán, Alberto; Avila, Jesús (Frontiers in Aging Neuroscience, 2020)
Human tauopathies, such as Alzheimer’s disease, have been widely studied in transgenic mice overexpressing human Tau in the brain. The longest brain isoforms of Tau in mice and humans show 89% amino acid identity; however, the expression of the the isoforms of this protein in the adult brain of the two species differs. Tau 3R isoforms are not present in adult mice. In contrast, the adult human brain contains Tau 3R and also Tau 4R isoforms. In addition, the N-terminal sequence of Tau protein in mice and human differs, a Tau peptide (residues 17-28) being present in the former but absent in the latter. Here we review the main published data on this N-terminal sequence that suggest that human and mouse Tau proteins interact with different endogenous proteins and also show distinct secretion patterns.